Hepatic artery reconstruction using an operating microscope in pediatric liver transplantation—Is it worth the effort?. (31st October 2021) - Dziodzio, Tomasz; Martin, Friederike; Gül‐Klein, Safak; Globke, Brigitta; Ritschl, Paul Viktor; Jara, Maximilian; Hillebrandt, Karl‐Herbert; Nösser, Maximilian; Koulaxouzidis, Georgios; Fehrenbach, Uli; Gratopp, Alexander; Henning, Stephan; et al.
Abstract: Introduction: In pediatric liver transplantation (pLT), hepatic artery thrombosis (HAT) is associated with inferior transplant outcome. Hepatic artery reconstruction (HAR) using an operating microscope (OM) is considered to reduce the incidence of HAT. Methods: HAR using an OM was compared to a historic cohort using surgical loupes (SL) in pLT performed between 2009 and 2020. Primary endpoint was the occurrence of HAT. Secondary endpoints were 1‐year patient and graft survival determined by Kaplan–Meier analysis and complications. Multivariate analysis was used to identify independent risk factors for HAT and adverse events. Results: A total of 79 pLTs were performed [30 (38.0%) living donations; 49 (62.0%) postmortem donations] divided into 23 (29.1%) segment 2/3, 32 (40.5%) left lobe, 4 (5.1%) extended right lobe, and 20 (25.3%) full‐size grafts. One‐year patient and graft survival were both 95.2% in the OM group versus 86.2% and 77.8% in the SL group ( p  = .276 and p  = .077). HAT rate was 0% in the OM group versus 24.1% in the SL group ( p  = .013). One‐year patient and graft survival were 64.3% and 35.7% in patient with HAT, compared to 93.9% and 92.8% in patients with no HAT (both p  < .001). Multivariate analysis revealed HAR with SL ( p  = .022) and deceased donor liver transplantation (DDLT) ( p  = .014) as independent risk factors for HAT. The occurrence of HAT was independently associated with the need for retransplantation ( p  < .001) and biliary leakage ( p  = .045). Conclusion: In pLT, the use of an OM is significantly associated to reduce HAT rate, biliary complications, and graft loss and outweighs the disadvantages of delayed arterial perfusion and prolonged warm ischemia time (WIT).